Physicochemical properties, toxicity and larvicidal activity of the essential oil of Cymbopogon winterianus in front of Aedes aegypti - Costa, Gabriela Morais da; Santos, Maria Conceição Carneiro dos; Everton, Gustavo Oliveira; Sousa, Paulina de Cássia Duarte de; Rangel, Maurício Eduardo Salgado (Ciência e Natura, 2022)
Due to the increasing rate of morbidity and mortality caused by vector diseases in the current context, especially by Aedes aegypti, substances of plants have been studied as alternatives to chemical insecticides, among them, the essential oil (EO) of the species Cymbopogon winterianus. Thus, this study evaluated the larvicidal activity of the EO of C. winterianus against the A. aegypti larvae. EO was extracted through the hydro-distillation technique and physicochemical properties were determined. To evaluate larvicidal activity, tests were performed with larvae in the third instar at the final concentrations of 19.54; 26.50; 55.59; 138.98; 208.47 and 277.97 mg L-1 of C. winterianus EO. In addition, Artemia salina Leach bioassay was used to verify toxicity effect. EO obtained presented satisfactory results in 2.64%. In the larvicidal assay, 100% mortality of larvae was observed after 24 hours at concentrations of 208.47 mg L-1 and 277.97 mg L-1 of the EO, showed effective in the other concentrations and with LC50 of 46.18 mg L-1, considered highly active. In the toxicity assay, the EO presented LC50 at 532.34 mg L-1, showed considered nontoxic. These results reinforce the use of EO front A. aegypt larvae control.